Analisis Perbedaan Kebijakan Pendanaan dan Dividen antara Perusahaan Tumbuh dan Tidak Tumbuh dengan Pendekatan IOS (Studi pada Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2015) - Zazilatul Mu'mila; Tatang Ary Gumanti; Novi Puspitasari (UPT Penerbitan Universitas Jember, 2019)
This study aims to analyze differences in funding policy as measured by debt equity ratio, and debt to market value equity then funding policy as measured by dividend payout ratio and dividend yield. The growth companies and non growth companies. The population in this research is property and real estate companies listed on the Indonesia Stock Excange years 2012-2015, sampling technique is purposive sampling so that obtained 123 data that meet the completeness of research data. The analytical method used comfirmatory factor analysis and different test analysis. Hypothesis test was done by independent sample t test and U-Mann Whitney test. The results show that debt equity ratio and dividend payout ratio there is no significant difference between growth companies and non growth companies. While debt to market value equity and dividend yield. There is a significant difference between growth companies and non growth companies. Keywords: Proxy IOS, DER, D/MVE, DPR and DY.